A random waveness model for the stiffness and strength evaluation of 3D woven composites. (15th September 2016) - Zhong, Suyang; Guo, Licheng; Liu, Gang; Zhang, Li; Pan, Shidong
Abstract: Three-dimensional (3D) woven composites are typical anisotropic textile composites and their mechanical properties mainly depend on the distribution and the mechanical properties of the fiber yarns. An important phenomenon should be emphasized that the fiber yarns usually deviate from their designed positions during the manufacturing process, which results in the random waviness of the fiber yarns. In some cases, these waviness phenomena may affect the mechanical responses significantly. In this paper, a random waviness model (RW model) is proposed which consider the fiber yarns' random waviness to investigate the stiffness and strength of 3D woven composites. Based on the actual statistics of the fiber yarns' random waviness, the stiffness and strength of a type of 3D woven composites are predicted and the corresponding experiments are also carried out. The predicted results agree well with the experimental ones. The variations of the modulus and the strength with the random characteristics of the fiber yarns' waviness are discussed. Results show that the random waviness of fiber yarns should be taken into consideration for actual 3D woven composites and the present method is very useful for the prediction of the mechanical properties of 3D woven composites.